Impact of germination on structural, physicochemical, techno-functional, and digestion properties of desi chickpea (Cicer arietinum L.) flour. (30th March 2023) - Sofi, Sajad Ahmad; Rafiq, Shafiya; Singh, Jagmohan; Mir, Shabir Ahmad; Sharma, Sushil; Bakshi, Parshant; McClements, David Julian; Mousavi Khaneghah, Amin; Dar, B.N.
Graphical abstract: Highlights: Germination altered the nutritional profile of chickpea flour. Germination increased protein and fiber content but reduced ash content. Germination improved the functional properties and in vitro digestibilitGermination decreased the antinutritional factors in chickpea flour. Germination reduced starch crystallinity in chickpea flour. Abstract: Germination significantly increased the nutrient composition, total phenolic content, and antioxidant activity of the chickpea flour cultivars studied (GNG-469 and GNG-1581). Protein and starch digestibilities were significantly improved in germinated chickpea flour. Germinated chickpea flour formed gels that had a shear modulus about 60% that of the non-germinated ones. X-ray diffraction analysis indicated that both A and B type polymorphs were present in the chickpea flour cultivars. Germination significantly reduced the relative crystallinity of the chickpea flour cultivars, from around 33 to 27% for GNG 469 and around 30 to 25% for GNG 1581. Protein secondary structures showed increase in β-sheets and random coils content in chickpea cultivars during germination. Phenolic acid profiling showed a decrease in the concentration of ellagic, p-coumaric, p-hydroxybenzoic, and caffeic acids but an increase in gallic, p-coumaric, and ferulic acids after germination.